Immunological study of the regulation of cellular arylsulfatase synthesis in Klebsiella aerogenes. - Murooka, Y (1977)
Regulation of cellular arylsulfatase synthesis in Klebsiella aerogenes was analyzed by immunological techniques. Antibody directed against the purified arylsulfatase from K. aerogenes W70 was obtained from rabbits and characterized by immunoelectrophoresis, double-diffusion, quantitative precipitation, and enzyme neutralization tests. Arylsulfatase was located in the periplasmic space when the wild-type strain was cultured with methionine or with inorganic sulfate plus tyramine, but not with inorganic sulfate without tyramine, as the sole sulfur source. Tyramine oxidase was retained in the membrane fraction prepared from cells grown in the presence of tyramine. Arylsulfatase protein was not synthesized in the presence of tyramine and inorganic sulfate by mutant K611, which is deficient in tyramine oxidase (tynA). We conclude that the expression of the arylsulfatase gene (atsA) is regulated by the expression of tynA and that inorganic sulfate serves as a corepressor. In addition, strains mutated in the atsA gene were analyzed by using antibody.